تأثير استخدام يوتيوب في فهم الأقصوصة العربية لدى الطلبة الناطقين بغير اللغة العربية - Fudzla Suraiyya Abdul Raup (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study aimed to determine the effectiveness of using YouTube in understanding Arabic Storiettes and to discover students' perceptions towards using YouTube in understanding Arabic Storiettes. The researcher depends on descriptive and analysis methods to complete this study. A total of 66 form six students participated in this study. A test and questionnaire were constructed to accomplish study's objectives, and the datas collected were analysed using SPSS. The result had shown that there are significant difference in test marks between control and experimental groups, and it was discovered that experimental group's results are better than the control group. Furthermore, the result also showed that there are significant difference in experimental group's results between animal story session and moral story session, whereas students' results in animal story test are better than moral story test. In addition, the questionnaire's result showed that most of the students agree that YouTube helps them in understanding Arabic Storiettes. Based on the results for this study, the researcher recommended further researches focusing on utilizing Web 2.0 in teaching and learning Arabic Language because it can help students in improving their language skills, increasing their understanding and motivating them to learn. Keywords: Web 2.0, YouTube, Arabic Storiettes.